Success Story Of Mission Indra Dhanush: A Road to Achieve Universal Immunization - Md Abu Bashar (Medsci Publications, 2016)
In order to improve the improve the immunization coverage of children under 2 years of age and to provide universal immunization to children from migratory population, Government of India launched mission Indradhanush in December 2014 as a special drive to vaccinate all unvaccinated and partially vaccinated children and pregnant women by 2020. A total of 201 high focus districts where more than 50% of the total unvaccinated or partially vaccinated children live were identified for covering under phase one of this drive. A total of 7.6 million children were vaccinated in this phase out of which 1.9 million got fully immunized. Second phase of the drive have also completed recently in 352 districts of the country. Seeing its wider coverage, mission Indradhanush has been success till now.